2018
DOI: 10.1039/c8nr02861c
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of thrombolytic therapy using rod-shaped plant viral nanoparticles decreases the risk of hemorrhage

Abstract: Cardiovascular thrombotic disease is an underlying cause of stroke, myocardial infarction and pulmonary embolism - some of the leading causes of death worldwide. Reperfusion therapy with anticoagulant, antiplatelet, and fibrinolytic agents has significantly reduced early mortality and morbidity from acute myocardial infarction and stroke. Nevertheless, bleeding side effects (e.g., intracranial hemorrhage) associated with the anti-thrombotic therapy can offset its benefits and limit its applicability to strictl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 47 publications
(79 reference statements)
0
26
0
Order By: Relevance
“…Illumination of the right carotid artery of C57BL/6 mice with a 540 nm green laser produced thrombi. TMV-tPA was delivered via tail vein injection and maintained its efficacy and performed similarly to free tPA; more importantly, the TMV-tPA formulations displayed an improved safety profile indicated by a decreased average bleeding time of 429 s to 858 by the free tPA [94]. The decreased bleeding time is of noteworthy importance as tPA does not specifically congregate at the diseased area, and systemic administration can lead to life-threatening systemic hemorrhaging and/or angioedema [95].…”
Section: Delivery Of Peptides and Protein Drugsmentioning
confidence: 99%
“…Illumination of the right carotid artery of C57BL/6 mice with a 540 nm green laser produced thrombi. TMV-tPA was delivered via tail vein injection and maintained its efficacy and performed similarly to free tPA; more importantly, the TMV-tPA formulations displayed an improved safety profile indicated by a decreased average bleeding time of 429 s to 858 by the free tPA [94]. The decreased bleeding time is of noteworthy importance as tPA does not specifically congregate at the diseased area, and systemic administration can lead to life-threatening systemic hemorrhaging and/or angioedema [95].…”
Section: Delivery Of Peptides and Protein Drugsmentioning
confidence: 99%
“…Functioned efficiently equivalent to free tPA and enhanced safety profile as shown by diminished average bleeding times and therefore applicable for cardiovascular therapy [81] (b) Applications of TMV in cancer treatment…”
Section: (A) Applications Of Tmv In Medicine Engineered Modifications Effects Referencementioning
confidence: 99%
“…Subsequently, through intramyocardial injection and magnetic guidance, the nanovesicles successfully promote early transfer from the inflammation promotion phase to the reparative phase, significantly alleviate apoptosis and fibrosis, and enhance the healing of cardiac function. In addition, Pitek et al indicated that one plant viral NPs can also target thrombi and exhibited their capability for streptokinase delivery in thrombosis model animals ( Pitek et al, 2018 ).…”
Section: Nanomedicines For Drug Deliverymentioning
confidence: 99%